Role of physical and mechanical properties of stainless steels in expected thermal fatigue life of plenum barrier plate of a gas turbine frame - Rashid A.Z.; Purbolaksono J.; Ramesh S.; Hamdi M.; Ahmad A.; Tarlochan F. (2023)
[No abstract available]